Degree Requirement & Employment Opportunity in Radiologic Science. - Weening, Richard H. (Radiologic Technology)
Objective To estimate the short-term effect of increasing the minimum education requirement for primary certification examination eligibility on employment opportunities in the radiologic sciences in the United States. Methods Data was gathered from the websites of academic institutions, accrediting agencies, and certification bodies to determine the percentages of education programs that offer radiologic technology students certificates, associate degrees, bachelor's degrees, or master's degrees. Results Approximately one-third of radiologic science education programs currently award certificates to their graduates. Discussion Some certificate programs appear to be reacting slowly to the increasing of the minimum education requirement. In addition, there appears to be some recent cutbacks in the total number of professional education programs. Perhaps unfortunately, the time frame in which many education programs have been attempting to transition to award students an associate degree upon program completion has coincided with the recent period of global economic turmoil. Conclusion The short-term effect of increasing the minimum education requirement on radiologic science employment opportunities could be large and non-negligible. Thus, employment opportunities for imaging professionals could grow faster than currently projected, as the supply of graduates meeting the increased minimum education requirement of an associate degree could be limited in the short term.